(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The advent of digital currencies has been a transformative phenomenon in the world of finance, marking a significant shift from traditional fiat currencies to innovative, technology-driven alternatives. Among these, cryptocurrencies, led by Bitcoin, and stable coins have garnered considerable attention, while Central Banks have begun exploring the concept of Central Bank Digital Currencies (CBDCs). This article delves into the rise of digital currencies, examining the evolution of cryptocurrencies, the emergence of stable coins, and the potential of CBDCs, highlighting both the benefits and challenges associated with these novel forms of exchange.